PRINSIP DAKWAH NABI MUHAMMAD SAW DALAM KONTEKS MAKKAH DAN MADINAH - Alif Rohmah Nur Habibah (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2023)
Islamic da'wah has a long history since the history of mankind, the prophets and apostles sent by Allah SWT from time to time depict an endless series of Islamic da'wah, many examples (uswah) can be taken from the life of the Prophet Muhammad's da'wah. Because basically he was sent on this earth to regulate the order of humanity so that it is in harmony with the rules of Allah SWT. This character radiated from the noble personality of the Prophet and was reflected clearly in his preaching activities and in the life of society and the state at that time. The purpose of writing this scientific work is to find out how the Prophet Muhammad struggled and how to preach in Mecca and Medina. This research method uses a historical method with four research stages, namely, first, searching for documents, second, criticizing documents, third, interpreting or interpreting, and fourth, presentation in the form of historiography. The results of this research are that there were many ways in which the Prophet preached in the cities of Mecca and Medina so that he could successfully spread, maintain and strengthen the religion of Islam in the people of Mecca and Medina. From his character in preaching, the principles of his preaching were also factors in his success. in preaching. Then, through the Prophet's preaching letters to regional rulers, it had a huge impact on the expansion of the Islamic region.